The Effect of Plank Training With The Concept of Training from Home During The Covid-19 Pandemic - Sifaq, Aghus; Kusuma, I Dewa Made Aryananda Wijaya; Wahyudi, Achmad Rizanul; Khamidi, Amrozi; Yuhantini, Eva Ferdita (Universitas Negeri Semarang, 2020)
The Covid-19 pandemic that hit Indonesia, made people have to limit activities outside the home, including athletes who have to maintain their physical quality. With the implementation of large-scale social restrictions, all athletes are required to continue training even though it is done at their respective homes. Training from home is a way for athletes to maintain their condition at home. This study aims to determine the effect of plank training through the concept of training from home which is carried out on athletes who come to the provincial sports week (Porprov) in Tuban during the Covid-19 pandemic. The method used was an experimental design with a randomized control group pretest-posttest design, the sample of this study involved 24 male athletes who were born in Tuban porprov which were divided into two groups, namely the treatment group and the control group. The results of the data analysis showed an increase by an average of 3.84 meters in the treatment group and 0.02 meters in the control group. Based on the results and discussion, it can be concluded that plank training using the training from home concept has a significant improvement